Weiterbildung als Co-Kreation – Kollegiale Interaktionsräume im Kontext eines Forschungs- und Entwicklungsprojektes zu Selbstinszenierung im Übergang Schule-Beruf - Kundisch, Heike; Otto, Franziska (bwp@ Spezial 21: Trilaterales Doktorandenseminar der Wirtschaftspädagogik Köln, Paderborn und des BIBB – Einblicke in Forschungsarbeiten)

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Transporting behavioral insights to low-income households: A field experiment on energy efficiency investments - Kesternich, Martin; Chlond , Bettina; Goeschl, Timo; Werthschulte, Madeline
Many industrialized countries have recognized the need to mitigate energy cost increases faced by low-income households by fostering the adoption of energy-efficient technologies. How to meet this need is an open question, but “behavioral insights” are likely components of future policy designs. Applying well-established behavioral insights to low-income house- holds raises questions of transportability as they are typically underrepresented in the existing evidence base. We illustrate this problem by conducting a randomized field experiment on scalable, low-cost design elements to improve program take-up in one of the world’s largest en- ergy efficiency assistance programs. Observing investment decisions of over 1,800 low-income households in Germany’s “Refrigerator Replacement Program”, we find that the transportabil- ity problem is real and consequential: First, the most effective policy design would not have been chosen based on existing behavioral insights. Second, design elements favored by these insights either prove ineffective or even backfire, violating ‘do no harm’ principles of policy advice. Systematic testing remains crucial for addressing the transportability problem, partic- ularly for policies targeting vulnerable groups.
Keywords: Transportability; low-income households; field experiment; randomized controlled trial; governmental welfare programs; energy efficiency; technology adoption

Digital Dotted Lines: Design and Evaluation of a Prototype for Digitally Signing Documents Using Identity Wallets - Last, Yorick; Geels, Jorrit; Schraffenberger, Hanna (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems (CHI EA ’24))
Documents are largely stored and shared digitally. Yet, digital documents are still commonly signed using (copies of) handwritten signatures, which are sensitive to fraud. Though secure, cryptography-based signature solutions exist, they are hardly used due to usability issues. This paper proposes to use digital identity wallets for securely and intuitively signing digital documents with verified personal data. Using expert feedback, we implemented this vision in an interactive prototype. The prototype was assessed in a moderated usability test (𝑁 = 15) and a subsequent unmoderated remote usability test (𝑁 = 99). While participants generally expressed satisfaction with the system, they also misunderstood how to interpret the signature information displayed by the prototype. Specifically, signed documents were also trusted when the document was signed with irrelevant personal data of the signer. We conclude that such unwarranted trust forms a threat to usable digital signatures and requires attention by the usable security community.

Optimizing Communication for Latency Sensitive HPC Applications on up to 48 FPGAs Using ACCL - Meyer, Marius; Kenter, Tobias; Petrica, Lucian; O’Brien, Kenneth; Blott, Michaela; Plessl, Christian (Lecture Notes in Computer Science)
Abstract Most FPGA boards in the HPC domain are well-suited for parallel scaling because of the direct integration of versatile and high-throughput network ports. However, the utilization of their network capabilities is often challenging and error-prone because the whole network stack and communication patterns have to be implemented and managed on the FPGAs. Also, this approach conceptually involves a trade-off between the performance potential of improved communication and the impact of resource consumption for communication infrastructure, since the utilized resources on the FPGAs could otherwise be used for computations. In this work, we investigate this trade-off, firstly, by using synthetic benchmarks to evaluate the different configuration options of the communication framework ACCL and their impact on communication latency and throughput. Finally, we use our findings to implement a shallow water simulation whose scalability heavily depends on low-latency communication. With a suitable configuration of ACCL, good scaling behavior can be shown to all 48 FPGAs installed in the system. Overall, the results show that the availability of inter-FPGA communication frameworks as well as the configurability of framework and network stack are crucial to achieve the best application performance with low latency communication.

On the global impact of Erich Mendelsohn’s architecture. Sergio Larraín’s Oberpaur building in Santiago and the beginnings of modernist architecture in Chile - Silvestri, Marco (Positioning: Erich Mendelsohn and the Built Heritage of the 20th Century)

Highly dynamic force control for experimental vibration analysis with an electrodynamic shaker Hochdynamische Kraftregelung für die experimentelle Schwingungsanalyse mit einem elektrodynamischen Shaker - Lüke, Christopher; Trächtler, Ansgar (Forschung im Ingenieurwesen)
Abstract A new control method aims at the precise high dynamic control of the force signal for experimental vibration analysis, which is generated by an electrodynamic shaker. A bending beam is used as a nonlinear test object. A design and a surrogate model of the test rig are shown and parameterized based on test rig measurements. The force control algorithm using input/output linearisation is described and implemented in Matlab/Simulink for simulative validation studies. Conclusions drawn from the mathematical description of the problem as well as simulation results show that the design of the contact between shaker and test object is crucial to achieve a high control bandwidth and at the same time reduce the energy consumption of the shaker. This leads to the practical application using a novel damping contact element. Finally, experimental test rig results are presented which show a closed loop bandwidth of at least 250 Hz for sinusoidal excitation signals.

Expulsion prevention in resistance spot welding of dissimilar joints with ultra-high strength steel: An analysis of the mechanism and effect of preheating current - Yang, Keke; El-Sari, Bassel; Olfert, Viktoria; Wang, Zhuoqun; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing Processes)
The widespread adoption of ultra-high strength steels, due to their high bulk resistivity, intensifies expulsion issues in resistance spot welding (RSW), deteriorating both the spot weld and surface quality. This study presents a novel approach to prevent expulsion by employing a preheating current. Through characteristic analysis of joint formation under critical welding current, the importance of plastic material encapsulation around the weld nugget (plastic shell) at high temperatures in preventing expulsion is highlighted. To evaluate the effect of preheating on the plastic shell and understand its mechanism in expulsion prevention, a two-dimensional welding simulation model for dissimilar ultra-high strength steel joints was established. The results showed that optimal preheating enhances the thickness of the plastic shell, improving its ability to encapsulate the weld nugget during the primary welding phase, thereby diminishing expulsion risks. Experimental validation confirmed that by employing the optimal preheating current, the maximum nugget diameter was enhanced to 9.42 mm, marking an increase of 13.4 % and extending the weldable current range by 27.5 %. Under quasi-static cross-tensile loading, joints with preheating demonstrated a 7.9 % enhancement in maximum load-bearing capacity compared to joints without preheating, showing a reproducible and complete pull-out failure mode within the heat-affected zone. This study offers a prevention method based on underlying mechanisms, providing a new perspective for future research on welding parameter optimization with the aim of expulsion prevention.
Keywords: Expulsion Resistance spot welding Finite element modelling Preheating Weldable current range Ultra-high strength steel

Steuerwettbewerb als Chance - Birnbaum, Kirsten; Heckemeyer, Jost H.; Linau, Annette; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

Too Complex to Cooperate? Tax Complexity and Cooperative Compliance - Schipp, Adrian
This study investigates whether, how, and under what conditions the expected positive association between cooperative compliance programs and tax compliance is attenuated by tax complexity. Many countries have implemented cooperative compliance programs to improve compliance, however, the effectiveness of these programs varies across countries. I expect and find that the complexity of a country's tax system might impair the compliance-enhancing impact of cooperative compliance programs. Using cross-country data of 57 countries, I find that cooperative compliance programs generally promote compliance, except in countries with highly complex tax codes. Moreover, these programs are positively associated with tax compliance even if tax procedures, such as tax filing and payment or tax audits, are highly complex. My findings suggest that cooperative compliance programs can compensate for mistrust caused by complex tax procedures and enhance compliance. However, they may not be effective tools to enhance compliance in complex tax codes.

Aus Geschehen ein Ereignis formen: Auswählen, Werten, Sortieren in der Geschichtserzählung - Süßmann, Johannes (Ordnungssysteme. Auswählen, Werten, Sortieren in den Kulturwissenschaften)
Keywords: Geschichtstheorie; Ereignisbildung; Begriffsbildung; Erzählung; Narratologie

The Downsides of Democracy? The Case of Tax Complexity - Giese, Henning; Schipp, Adrian
This study investigates the association between the political characteristics of countries and the complexity of the legal system. We use country-level measures of tax complexity, democracy indicators, and election results data and find that the degree of democracy is associated with higher overall complexity of tax systems. This association is driven by the complexity of tax regulations. Contrastingly, we document negative associations with the complexity of tax procedures such as tax filings or tax audits. Moreover, we find the association between democracy and tax system complexity to be inversely U-shaped, indicating strong autocracies and strong democracies to reduce overall tax complexity. In further analyses, we document that the complexity of anti-tax avoidance regulations increases with higher levels of democracy and demonstrate that left-wing governed countries are more prone to experience an increase in complexity through democracy than right-wing governed countries.

Broadband acoustic waves in plate-like structures for acoustic material characterisation - Claes, Leander; Johannesmann, Sarah; Zeipert, Henning; Henning, Bernd (2023 International Congress on Ultrasonics, Beijing, China)

A pulse-echo measurement setup to determine viscoelastic material parameters - Dreiling, Dmitrij; Itner, Dominik; Hetkämper, Tim; Birk, Carolin; Gravenkamp, Hauke; Henning, Bernd (2023 International Congress on Ultrasonics, Beijing, China)

Lernprozessanregende Aufgaben in der Lehrkräftebildung: Förderung von Reflexions- und Medienkompetenz mit Fellinis „8 ½“ - Aßmann, Sandra; Wiethoff, Christoph (Medien – Bildung – Forschung. Integrative und interdisziplinäre Perspektiven)

"So was gibt es bei uns nicht!" - Fachkultur als Treiber oder Barriere für Transfer von digitalen (Lehr-)Innovationen - Heidebrecht, Jana; Sloane, Hannah Sabrina (die hochschullehre)

"Contributing means investing in Spain" – Media campaigns on tax education in Spain after the transition to democracy - Schönhärl, Korinna (Themenportal Europäische Geschichte)
What can the tax authorities do to encourage citizens to pay their taxes more honestly? They can promote honest tax payments in the media! Such tax education, which is completely unfamiliar to German taxpayers, can look back on a long tradition in the USA, for example, and other countries. It has also been practised in Spain since the end of the 1960s and intensified after the transition to democracy. A Treasury television advertisement from 1990 allows an analysis of the narratives used by tax education in the young Spanish democracy. The intense and difficult struggle by state institutions for democratic, equal rights for all citizens even 15 years after Franco's death becomes obvious.
Keywords: Spanish History; Financial History; Tax History; Video as historical sources

How to foster Future Skills in independent learning phases? - Wengler, Katja; Koppitsch, Gerlinde; Freisleben-Teutschner, Christian F.; Hüther, Judith; Kidritsch, Anita; Neiske, Iris (Tag der Lehre | Inverted Classroom and Beyond 2024 - Innovative Lehrveranstaltungsformate. Das Curriculum der Zukunft gestalten)

Towards a One-Stop-Shop Solution for the Application of Data-Driven Value-Adding Services in Production - Redeker, Magnus; Quirin, Dennis; Schroeder, Rafael; Klausmann, Tobias; Löwen, Alexander; Wollbrink, Alexander; Stichweh, Heiko; Althoff, Simon; Bender, Amelie; Sextro, Walter; Hesse, Marc (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA))

SELBSTKONZEPT. "Stark bin ich. Das muss ich auch sein!" – Zugänge und Einblicke zum Selbstkonzept von Jugendlichen am Übergang Schule-Beruf - Otto, Franziska (Bildung und Beruf)